The Relevance of the Major Themes of Earnest Hemmingway’s Novel The Old Man and the Sea to the Modern Man: A Critical Perspective: Exploring Resilience and Spiritual Connections in Hemmingway's Masterpiece (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper intends to throw light on the relevance of the major themes of Earnest Hemmingway’s famous novel “The Old Man and the Sea” to the modern man. Santiago, the protagonist of the novel who displays great power to withstand hunger, pain and isolation, succeeds in hooking a marlin and fights with it in spite of his old age, exhaustion and pain. Unfortunately, he has to fight with the sharks as well. Finally, when the sharks eat away the marlin and leave him nothing but its carcase as he returns to shore. But still he displays a sense of contentment and shows the readers how they have to tolerate odds and despair in life. The novelist uses splendid imagery to show that unlike any other fish, the marlin was not just a fish but rather a spiritual entity from Santiago’s point of view. Marlin is depicted as his worthy opponent. Eventually, he kills the marlin considering that they are now equals and that the marlin is just like his brother. He suffers from a sense of guilt and loneliness for sailing farther into the deep sea, just to kill fish that he somehow loved closely. The novel’s punch line is that “a man can be destroyed but not defeated”.